A Quantitative Analysis of AI-Based Solutions in IT Program Management: Performance Metrics and Predictive Modeling (The Science Post, 2025)
This paper presents a comprehensive quantitative analysis of AI-based solutions in IT program management, with a focus on performance metrics and predictive modeling. As organizations increasingly integrate AI into their project management processes, it becomes essential to assess the effectiveness and efficiency of these tools. This study evaluates the impact of AI on key performance indicators (KPIs) such as project delivery time, resource allocation, cost efficiency, and risk management. The paper applies predictive modeling techniques to forecast project outcomes, identify potential bottlenecks, and optimize resource distribution. Data from real-world IT programs and AI implementations are analyzed to provide insights into how AI-driven tools can enhance decision-making, mitigate risks, and improve overall program performance. The findings suggest that AI can significantly improve IT program management by automating routine tasks, predicting risks, and providing actionable insights for better decision-making.